2022-LBA-677-ESGO Distribution and prognostic role of BRCA status in elderly ovarian cancer patients. (27th October 2022) - Tortorella, Lucia; Cappuccio, Serena; Marchetti, Claudia; Costantini, Barbara; Giannarelli, Diana; Vizzielli, Giuseppe; Pasciuto, Tina; Lorusso, Domenica; Scambia, Giovanni; Fagotti, Anna
Abstract : Introduction: Elderly patients with advanced ovarian cancer often receive suboptimal treatment with less radical surgery, due to the complexity and risks of primary debulking surgery (PDS). We know that complete resection is the most important independent factor affecting survival. There is an emerging role of BRCA status. BRCA mut patients are more chemosensitive while BRCA wt could better benefit of PDS. In this context it's important to evaluate the distribution of BRCA status in elderly patients and if its prognostic role is still maintained in this subgroup of patients. Methods: This is a retrospective single institution study evaluating patients with known germinal/somatic BRCA status. We are comparing clinical and surgical characteristics according to age groups. We are evaluating the prevalence of BRCA mut in the age groups, how it affects survival and chemosensitivity in order to understand if in elderly patients its prognostic role is still maintained Results: A total of 2089 patients were included in the analysis. Mean age of BRCAmut was 55.8 (SD=10.9) and 60.3 (SD=12) for BRCAwt (p<0.0001). The rate of BRCAmut decreases over age-range ( figure 1 ). 1850 patients were stage IIIC-IV and older women were less likely submitted to PDS (from 62.1% for <50 y to 23.4% for ≥80 y), however the rate of complete resection was superimposable in all age range. Median Progression Free Survival (PFS) in women >65 y for PDS and IDS was respectively 29.7 vs 23.4 months (p=0.66) for BRCAmut, and 21.0 vs 15.4 months (p=0.004) for BRCAwt. Conclusions: BRCAmut is often associated to younger age, reaching the 50% in patients <50 y, however the rate of mutation in older age is not trascurable. BRCAmut patients maintain the best prognosis even in the older group. BRCAwt are less likely to respond to chemotherapy and in this group upfront surgery with complete resection makes the difference.